AN UNUSUAL CASE PRESENTATION: MALIGNANT THYROID NODULE IN A PATIENT WITH LUNG ADENOCARCINOMA - Putri, Poppy Permata; Decroli, Eva; Aprilia, Dinda; Kam, Alexander; Efendi, Yanne Pradwi; Syahbuddin, Syafril (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Lung adenocarcinoma is a prevalent subtype of lung cancer known for its capacity to metastasize to various organs. In patients diagnosed with this cancer, thyroid nodules pose diagnostic challenges, as they may indicate metastasis or represent distinct conditions such as multinodular goiter or other thyroid malignancies. Notably, lung adenocarcinoma has a higher tendency to metastasize to the thyroid, with an incidence rate of 1–3%. CASE A 53-year-old female, undergoing chemotherapy for lung adenocarcinoma, presented to the Internal Medicine Clinic at RSUP M. Djamil Padang with a secondary thyroid nodule suspected to be metastatic. Other differential diagnoses were primary thyroid tumor and subclinical hyperthyroidism. Her history included a neck mass, hoarseness, pain while swallowing, weight loss, fatigue, and tremors. Physical examination revealed multiple nodules in the anterior neck with defined borders that moved during swallowing. Thyroid ultrasound indicated bilateral multinodular goiter (TIRADS III) without lymph node enlargement. Scintigraphy showed a cold nodule. Fine needle aspiration biopsy (FNAB) confirmed thyroid carcinoma consistent with metastasis from lung adenocarcinoma. The management plan included continuing chemotherapy and oncology consultation. CONCLUSION This case highlights the critical importance of early detection and management of secondary cancers to enhance patient outcomes and emphasizes the need for clinician awareness of thyroid metastasis in lung cancer, particularly lung adenocarcinoma.